2012
DOI: 10.1182/blood-2011-10-386235
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of a HOXA-PBX3 homeobox-gene signature following down-regulation of miR-181 is associated with adverse prognosis in patients with cytogenetically abnormal AML

Abstract: Increased expression levels of miR-181 family members have been shown to be associated with favorable outcome in patients with cytogenetically normal acute myeloid leukemia. Here we show that increased expression of miR-181a and miR-181b is also significantly (P < .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
158
2
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 150 publications
(173 citation statements)
references
References 48 publications
(88 reference statements)
10
158
2
3
Order By: Relevance
“…It appears to be the most critical member of PBX family contributing to leukaemogenesis by serving as a cofactor of other homeodomain proteins such as HOX and MEIS 34,35 to control gene expression, and has been identified as a direct target of let-7c, miR-181a/miR-181b, to function in colorectal cancer metastasis and leukaemogenesis, respectively 36,37 . Hence, PBX3 was chosen to validate further whether it was directly targeted by the four miRNAs to regulate a2d1 þ HCC TICs.…”
Section: Resultsmentioning
confidence: 99%
“…It appears to be the most critical member of PBX family contributing to leukaemogenesis by serving as a cofactor of other homeodomain proteins such as HOX and MEIS 34,35 to control gene expression, and has been identified as a direct target of let-7c, miR-181a/miR-181b, to function in colorectal cancer metastasis and leukaemogenesis, respectively 36,37 . Hence, PBX3 was chosen to validate further whether it was directly targeted by the four miRNAs to regulate a2d1 þ HCC TICs.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that expression of miR-181b is associated with lower CR rates and shorter relapse-free survival (RFS) and OS in adult patients with de novo AML (25). Multivariable analysis has revealed that increased expression of miR-181a and miR-181b is also significantly associated with favorable outcomes in cytogenetically abnormal AML with CEBPA mutations and cytogenetically normal AML patients (26)(27)(28)(29). However, an obvious increase of miR-181b-5p was observed in AML serum samples and that higher expression levels of miR-181b-5p in serum are correlated with a poorer OS (30).…”
Section: Discussionmentioning
confidence: 99%
“…Although HOXA overexpression has been linked to adverse prognosis in acute myeloid leukemia, [30][31][32][33] the clini-ETP predicts outcome in HOXA-positive adult T-ALL. …”
Section: Discussionmentioning
confidence: 99%